Influence of different probiotics treatment on the quality of seawater reared with milkfish (chanos chanos) fry. - Gatilogo, Katherine M. (College of Fisheries, University of the Philippines, 2013)
Deterioration of water quality had been one of the reasons of the mortality and low survival of milkfish fry and juvenile and can contribute to the occurrence of disease. The use o commercial probiotics has been recognized as an alternative approach for the improvement of water quality. This study utilized the commercially available BZT Aquaculture, Uni-Ecosafe and red Bacteria probiotics to treat seawater stocked with chanos-chanos fry. Four treatments were used in the experiment- treatments A, B, C and D. treatments A, B AND C utilized BZT Aquaculture Probiotics, Uni-Ecosafe probiotics and red bacteria respectively with the concentration of 3 ppm each. Treatment D, on the other hand, was not treated and served as control. Water quality such as ammonia-N, reactive nitrate, dissolve oxygen and salinity was monitored every 3rd day, days before every application of probiotics has significance on the reduction of ammonia and nitrite concentration, suspension of the salinity and dissolved oxygen fluctuation, and growth enhacement of milkfish fry. However, statistical analysis on survival rate of milkfish shows no significance. Graph suggests that probiotics was able to improve water quality of seawater and enhance the growth and survival of milkfish fry.